Respostas
respondido por:
5
an = a1 + (n-1).r
a4 = a1 + 3r
12 = a1 + 3r ⇒ a1 = 12 - 3r
a9 = a1 + (n-1).r
a9 = a1 + 8r
27 = a1 + 8r ⇒ a1 = 27 - 8r
como a1 = a1, temos:
12 - 3r = 27 - 8r
8r - 3r = 27 - 12
5r = 15
r = 3
Substituindo a1 = 12 - 3r ⇒ a1 = 12 - 3.3 ⇒ a1 = 12 - 9 ⇒ a1 = 3
a5 = a1 + (n-1).r
a5 = 3 + 4.3
a5 = 3 + 12
a5 = 15
Espero ter ajudado.
a4 = a1 + 3r
12 = a1 + 3r ⇒ a1 = 12 - 3r
a9 = a1 + (n-1).r
a9 = a1 + 8r
27 = a1 + 8r ⇒ a1 = 27 - 8r
como a1 = a1, temos:
12 - 3r = 27 - 8r
8r - 3r = 27 - 12
5r = 15
r = 3
Substituindo a1 = 12 - 3r ⇒ a1 = 12 - 3.3 ⇒ a1 = 12 - 9 ⇒ a1 = 3
a5 = a1 + (n-1).r
a5 = 3 + 4.3
a5 = 3 + 12
a5 = 15
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás